Concurrent recording of RF pulses and gradient fields – comprehensive field monitoring for MRI. (13th August 2015) - Brunner, David O.; Dietrich, Benjamin E.; Çavuşoğlu, Mustafa; Wilm, Bertram J.; Schmid, Thomas; Gross, Simon; Barmet, Christoph; Pruessmann, Klaas P.
Abstract : Reconstruction of MRI data is based on exact knowledge of all magnetic field dynamics, since the interplay of RF and gradient pulses generates the signal, defines the contrast and forms the basis of resolution in spatial and spectral dimensions. Deviations caused by various sources, such as system imperfections, delays, eddy currents, drifts or externally induced fields, can therefore critically limit the accuracy of MRI examinations. This is true especially at ultra‐high fields, because many error terms scale with the main field strength, and higher available SNR renders even smaller errors relevant. Higher baseline field also often requires higher acquisition bandwidths and faster signal encoding, increasing hardware demands and the severity of many types of hardware imperfection. To address field imperfections comprehensively, in this work we propose to expand the concept of magnetic field monitoring to also encompass the recording of RF fields. In this way, all dynamic magnetic fields relevant for spin evolution are covered, including low‐ to audio‐frequency magnetic fields as produced by main magnets, gradients and shim systems, as well as RF pulses generated with single‐ and multiple‐channel transmission systems. The proposed approach permits field measurements concurrently with actual MRI procedures on a strict common time base. The combined measurement is achieved with an array of miniaturized field probes that measure low‐ to audio‐frequency fields via 19 F NMR and simultaneously pick up RF pulses in the MRI system's 1 H transmit band. Field recordings can form the basis of system calibration, retrospective correction of imaging data or closed‐loop feedback correction, all of which hold potential to render MRI more robust and relax hardware requirements. The proposed approach is demonstrated for a range of imaging methods performed on a 7 T human MRI system, including accelerated multiple‐channel RF pulses. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : By using NMR field probes in conjunction with broadband RF receivers, a stand‐alone monitoring unit measuring RF pulses and gradient waveforms concurrently and with common timing was built. The unit can capture the field dynamics of multi‐channel RF transmission systems without the need for dedicated RF pickups, and delivers a comprehensive sequence depiction as it is executed by the scanner. These abilities are exemplified by monitoring typically challenging applications such bSSFP, UTE and spatially selective parallel transmission pulses at 7 T.